2016
DOI: 10.1139/apnm-2015-0561
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning increases muscle perfusion, oxygen uptake, and force in strength-trained athletes

Abstract: Muscle ischemia and reperfusion induced by ischemic preconditioning (IPC) can improve performance in various activities. However, the underlying mechanisms are still poorly understood. The purpose of this study was to examine the effects of IPC on muscle hemodynamics and oxygen (O2) uptake during repeated maximal contractions. In a cross-over, randomized, single-blind study, 10 strength-trained men performed 5 sets of 5 maximal voluntary knee extensions of the right leg on an isokinetic dynamometer, preceded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
124
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(134 citation statements)
references
References 42 publications
7
124
3
Order By: Relevance
“…The present data demonstrated clear differences between sexes; compared with males, females exhibited a lower force decrement over the five sets of maximal, isokinetic contractions. The lack of change in males is in keeping with previous studies reporting no differences between SHAM and IPC conditions in the measured fatigue index, despite higher peak and mean power outputs during the first repetitions of a series of ten 6 s cycle sprints (Patterson et al, 2015), or higher average force during maximal voluntary knee extensions after IPC (Paradis-Deschenes et al, 2016). This apparent sex difference in response to IPC could be attributed in part to the fact that males increased their initial and total force leading to greater subsequent metabolic and ionic perturbations (Balsom et al, 1994; Glaister, 2005).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The present data demonstrated clear differences between sexes; compared with males, females exhibited a lower force decrement over the five sets of maximal, isokinetic contractions. The lack of change in males is in keeping with previous studies reporting no differences between SHAM and IPC conditions in the measured fatigue index, despite higher peak and mean power outputs during the first repetitions of a series of ten 6 s cycle sprints (Patterson et al, 2015), or higher average force during maximal voluntary knee extensions after IPC (Paradis-Deschenes et al, 2016). This apparent sex difference in response to IPC could be attributed in part to the fact that males increased their initial and total force leading to greater subsequent metabolic and ionic perturbations (Balsom et al, 1994; Glaister, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, extraneous infusion of adenosine, which is a key acting molecule released during IPC, preferentially enhances vasodilation of arterioles to type II fibers (Wunsch et al, 2000). Therefore, due to the greater O 2 extraction of type II fibers when highly perfused (Wilson et al, 1977), it has been suggested that these fibers might benefit more from an increase in blood perfusion than the more aerobic type I fibers (Faiss et al, 2013; Paradis-Deschenes et al, 2016), which could explain the higher Δ[HHb] avg in strength-trained males in the present study.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Early findings suggested enhanced oxygen delivery to be the primary mechanistic change induced by IPC; however, recent research has proposed that IPC might also affect neural drive to working skeletal muscle (Barbosa et al., ; Crisafulli et al., ; Cruz, de Aguiar, Turnes, Salvador, & Caputo, ; Cruz, Pereira, Lisboa, & Caputo, ; Paradis‐Deschênes et al., ; Tanaka et al ., ). Barbosa et al.…”
Section: Introductionmentioning
confidence: 99%